(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассмотрен подход к оценке метеорологических параметров по снимкам с метеорологических спутников и радиолокационной информации. Он основан на комплексном учете значений яркостных и текстурных характеристик в облачности по ИК-снимкам. Применение данного подхода показало, что результаты диагноза и прогноза облачности, осадков, скорости и направления ветра по информации с ИСЗ NOAA могут использоваться в прогностическом процессе региона. Restoration of meteorological fields under satellite and radar images of overcast The research that was carried out and supported with the earlier numerical analysis’ structures, according to the data of meteorological radio-locators and meteorological Earth satellites allows to make the conclusion about the determination of atmosphere processes of average scale. The developed methodology of complex data analysis and reveal the average-structural features of cloudiness give the opportunity to combine the existing methods of renewal and employ it in order to reach the short-term forecast weather tasks.